1993
DOI: 10.1002/nau.1930120208
|View full text |Cite
|
Sign up to set email alerts
|

Male sexual impotence in diabetes mellitus: vasculogenic versus neurogenic factors

Abstract: In an attempt to understand better the role of vascular and neurogenic alterations in the pathophysiology of diabetic impotence, 29 impotent male patients with diabetes mellitus (DM) were investigated by means of doppler ultrasound examination (DUE) of penile arteries, sacral evoked responses (SERs), peripheral nerve conduction studies, and, in most cases, nocturnal penile tumescence monitoring (NPTM). Fourteen patients showed isolated alterations of penile vascular supply, four isolated alterations of penile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 23 publications
1
7
0
4
Order By: Relevance
“…Benvenuti et al reported that vascular occlusion, more than nerve damage, plays a primary role in the pathophysiology of diabetic erectile failure. 10 His ®nding would then explain our results in patients with demonstrated ischemic vascular disease in their coronary arteries.…”
Section: Discussionmentioning
confidence: 71%
“…Benvenuti et al reported that vascular occlusion, more than nerve damage, plays a primary role in the pathophysiology of diabetic erectile failure. 10 His ®nding would then explain our results in patients with demonstrated ischemic vascular disease in their coronary arteries.…”
Section: Discussionmentioning
confidence: 71%
“…Patients with insulin-dependent diabetes and associated coronary artery disease have significantly more severe disease related to the cavernosal artery than noninsulin-dependent diabetic patients (47). Benvenuti et al (48) proposed that, in diabetic ED, vascular obstruction is a more important factor than nerve damage. The main complication of diabetes is atherosclerosis.…”
mentioning
confidence: 99%
“…Мужчины с признаками периферической нейропатии чаще стра дают ЭД, чем больные СД без нейропатии [24]. Ча стота диабетической нейропатии значительно выше у больных с ЭД, чем у пациентов с сохраненными эрекциями; часто, у больных СД наряду с нейроген-ным имеется и васкулогенный фактор развития ЭД [6]. Получены данные о поражении нервных воло кон кавернозных тел у больных СД; у мужчин, стра дающих СД, повышен адренергический тонус нерв ной системы.…”
Section: физиологические и биохимические проблемы эрекцииunclassified